Exploring the predictive role of teacher immediacy and stroke behaviors in English as a foreign language university students’ academic burnout - Derakhshan, Ali; Eslami, Zohreh R; Curle, Samantha; Zhaleh, Kiyana (Studies in second language learning and teaching, 2022)
To expand the literature on the rather new concept of student burnout, the present study examined the influence of teacher immediacy and stroke variables on English as a Foreign Language (EFL) students’ experience of burnout. To fulfill this aim, a group of 631 undergraduate EFL students from various universities in Iran answered questionnaires including the Immediacy Behavior Scale, the Student Stroke Scale, and the Maslach Burnout Inventory-Student Survey. The results of confirmatory factor analysis (CFA) of immediacy and burnout scales demonstrated the validity of the two scales in the Iranian EFL context. Subsequently, Pearson multiple correlation coefficients and structural equation modeling (SEM) were used to analyze the data. It was found that student burnout subscales negatively and significantly correlated with teacher immediacy and stroke subscales. Moreover, the results indicated that teacher immediacy and stroke variables, in combination with their subscales, could predict student burnout. On the whole, it can be concluded that teacher immediacy and stroke concepts, characterized as positive teacher interpersonal communication behaviors enhancing rapport and positive interaction between the teacher and students in EFL contexts, are potential preventers of negative student-related outcomes such as burnout.